Current advances and future prospects of cell reprogramming in progeroid syndromes - Moledo-Nodar, Lucas; Celemín-Capaldi, Víctor; Ugalde, Alejandro P.; Freije, José M. P. (Frontiers in Cell and Developmental Biology, 2025)
Cell reprogramming consists in the reverse process to cell differentiation, making cells lose their identity and age-related characteristics and granting an increased potential for proliferation and redifferentiation on different lineages. This process holds immense potential for the treatment of several pathologies, including progeroid syndromes, diseases that recapitulate the symptoms seen in physiological aging in an accelerated manner. Among the recent advances on the use of cell reprogramming in the context of progeroid syndromes, the interventions based on partial reprogramming, consisting on the dedifferentiation of cells only up to a point in which they lose age related characteristics but keep their identity, stand out. This partial reprogramming can be achieved both using the forced expression of transcription factors or cocktails of small molecules that regulate different biological processes. While all these advances are promising, the use of cell reprogramming in the treatment of progeroid syndromes still faces several challenges, such as the development of methods that allow for an efficient delivery of cell reprogramming factors in vivo and fine tuning of the dose used. Furthermore, these approaches should be accompanied by treatments targeting the original cause of the disease or they could be proven futile in the long term.